2015
DOI: 10.1007/s10854-014-2638-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alkali metal compound fluxes on Gd2O2S:Tb particle and luminescence

Abstract: Gd 2 O 2 S:Tb phosphors with different alkalimetal compound fluxes were synthesized by molten salt method, showing high luminous intensity, monodispersity and micron size characteristics. The results indicated that from K ? to Na ? and to Li ? , the particles mean size tended to grow bigger. K ? could effectively reduce the particle size without depressing the luminescence intensity. Meanwhile, after comparing the strongest emission intensity among different fluxes, it was shown that K ? had most significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…32,33 Also, Li 2 O or Li + is a typical network modifying agent, contributing to structural densification. [34][35][36][37] The reaction between the dopant and the matrix phase is studied and results show that the mechanism is exactly the same in all cases. Compared with Cs + , Li + is an intermediate cation with a stronger electric field intensity in glass-ceramics system.…”
Section: (4) Sintering Mechanismmentioning
confidence: 99%
“…32,33 Also, Li 2 O or Li + is a typical network modifying agent, contributing to structural densification. [34][35][36][37] The reaction between the dopant and the matrix phase is studied and results show that the mechanism is exactly the same in all cases. Compared with Cs + , Li + is an intermediate cation with a stronger electric field intensity in glass-ceramics system.…”
Section: (4) Sintering Mechanismmentioning
confidence: 99%
“…Meanwhile, the presence of carboxylate groups in the dysprosium organic complexes was confirmed by both the asymmetric vibration absorption peak (t asCOO-) at about 1597-1578 cm -1 and the symmetry vibration absorption peak (t sCOO-) at about 1429-1417 cm -1 . These experimental results showed that the carbonyl groups of carboxylic acid ligands were coordinated with the dysprosium ions [20]. In addition, the vibration absorption peak of C-H near 728 cm -1 of 1,10-phenanthroline shifted to lower wave number near 717-662 cm -1 .…”
Section: Structure and Composition Analysis Of Dy(lc) 3 Phenmentioning
confidence: 81%
“…The characteristic absorption peaks of phenanthroline and AA still exist in Eu(AA) 3 Phen; however, the absorption peak at 1699 cm −1 of CC disappears, and new absorption peaks around 1723, 1638, and 1429 cm −1 are detected, which are characteristic absorption peaks of CO bonds and COO groups, respectively. According to the relevant literature, 18 the absorption of these characteristic peaks is caused by the coordination of the carbonyl group of acrylic acid with the europium ion. Moreover, the peak of CN stretching absorption of Phen is red‐shifted from 1587 to 1576 cm −1 , indicating that nitrogen atoms in the Phen molecule also participate in coordination 19 .…”
Section: Resultsmentioning
confidence: 98%